2020
DOI: 10.1111/ajco.13372
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the predictive factors for anastomotic leakage after total laparoscopic resection with transrectal natural orifice specimen extraction for colorectal cancer

Abstract: Background: Natural orifice specimen extraction (NOSE) surgery has been widely implemented in colorectal cancer surgery due to its good short-term efficacy. However, anastomotic leakage (AL) is a serious postoperative complication in colorectal cancer, and the risk factors for this complication after NOSE surgery have rarely been investigated. The aim of this study was to explore the predictive factors for AL after laparoscopic resection with transrectal NOSE for rectal cancer and sigmoid colon cancer. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The robotic technique enhances the accuracy, flexibility, and precision of the NOSES procedure. Zhou et al (15) reported that 21 (10.1%) patients developed anastomotic leakage (AL) following laparoscopic resection with transrectal NOSE. The narrow pelvic cavity increased the complexity of the transrectal NOSE, such as intracorporeal This study showed that T4 stage cases accounted for 34.3% in the CRR group and 20.5% in the NOSES group, which is inconsistent with the recommendations of the International consensus on natural orifice specimen extraction surgery (NOSES) for colorectal cancer (10).…”
Section: Discussionmentioning
confidence: 99%
“…The robotic technique enhances the accuracy, flexibility, and precision of the NOSES procedure. Zhou et al (15) reported that 21 (10.1%) patients developed anastomotic leakage (AL) following laparoscopic resection with transrectal NOSE. The narrow pelvic cavity increased the complexity of the transrectal NOSE, such as intracorporeal This study showed that T4 stage cases accounted for 34.3% in the CRR group and 20.5% in the NOSES group, which is inconsistent with the recommendations of the International consensus on natural orifice specimen extraction surgery (NOSES) for colorectal cancer (10).…”
Section: Discussionmentioning
confidence: 99%
“…Both domestically and internationally, there is consensus on the impact of tumor location on AL following low anterior resection of rectal cancer; that is, the closer the tumor is to the anal margin, the higher the risk of AL[ 24 - 26 ]. The same conclusion was reached in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We also created the nomogram as a reference for clinicians and surgeons to help in clinical decision-making. Previous reports have described many potential risk factors for AL after colorectal cancer [ 17 , 18 , 20 , 34 ]. These risk factors include a wide range of factors in the perioperative period, and those predictive of preoperative factors alone have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…We searched the PubMed, Embase, and Web of Science databases without language or time restrictions to retrieve relevant studies. In some retrospective cohort studies and published reviews, based on the results of these articles, we selected some predictor variables that were assessable early at hospital admission [ 11 , 17 20 ], and these variables were combined with other preoperative factors added to the subsequent statistical analysis.…”
Section: Methodsmentioning
confidence: 99%